Emerging Voices: Encounters with Reflexivity - Hahn, Tomie (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
This paper focuses on the power of voice and the nature of reflexivity in feminist ethnography starting with a definition of reflexivity, a brief historical context, and closing with several mini-case studies, including Japanese traditional dance; Monster Truck rallies; and the Deep Listening community.